2019
DOI: 10.1093/jac/dkz437
|View full text |Cite
|
Sign up to set email alerts
|

β-Lactam pharmacodynamics in Gram-negative bloodstream infections in the critically ill

Abstract: Objectives To determine the β-lactam exposure associated with positive clinical outcomes for Gram-negative blood stream infection (BSI) in critically ill patients. Patients and methods Pooled data of critically ill patients with mono-microbial Gram-negative BSI treated with β-lactams were collected from two databases. Free minimum concentrations (fCmin) of aztreonam, cefepime, ceftazidime, ceftriaxone, piperacillin (co-admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 14 publications
2
30
0
4
Order By: Relevance
“…However, the unbound minimum concentration to MIC ratios (fC min /MIC) for these two intermittent regimens (0.0128 to 0.0256, respectively) were substantially below the fC min /MIC of ~ 2-6 that has been associated with suppression of resistance emergence for meropenem against P. aeruginosa in the HFIM 31 ; they were also below the fC min /MIC of > 1.3 reported as a significant predictor of a positive clinical outcome in critically ill patients with Gram-negative bloodstream infections. 32 For both meropenem intermittent regimens, treatment failure may be attributed to amplification of less-susceptible bacteria. Indeed, compared with the control arm there was a > 700,000-fold increase in meropenem less-susceptible bacteria when Pa1280 was exposed to regimens of 1 or 2 g q8h.…”
Section: Discussionmentioning
confidence: 99%
“…However, the unbound minimum concentration to MIC ratios (fC min /MIC) for these two intermittent regimens (0.0128 to 0.0256, respectively) were substantially below the fC min /MIC of ~ 2-6 that has been associated with suppression of resistance emergence for meropenem against P. aeruginosa in the HFIM 31 ; they were also below the fC min /MIC of > 1.3 reported as a significant predictor of a positive clinical outcome in critically ill patients with Gram-negative bloodstream infections. 32 For both meropenem intermittent regimens, treatment failure may be attributed to amplification of less-susceptible bacteria. Indeed, compared with the control arm there was a > 700,000-fold increase in meropenem less-susceptible bacteria when Pa1280 was exposed to regimens of 1 or 2 g q8h.…”
Section: Discussionmentioning
confidence: 99%
“…B. mit einer TDM-Strategie für Aminoglykoside bereits vor vielen Jahren in einem Allgemeinpatientenkollektiv zeigen, dass die Krankenhaus-Aufenthaltsdauer signifikant sinkt (20,3 vs. 26,3 Tage, p < 0,045) [40]. Aktuelle klinische Daten geben auch erste Hinweise für β-Lactam-Antibiotika, dass eine freie Wirkstoffkonzentration von 100 % des Dosisintervalls fT > 1x MHK < 4x MHK mit einem besseren Outcome verbunden ist [41,42]. [43].…”
Section: Merkeunclassified
“…Gerade vor dem Hintergrund des Erreichens adäquater Gewebekonzentration auch in tiefen Kompartimenten (z. B. Pneumonie) [27,47] und dem Vermeiden einer Resistenzentwicklung [32], empfehlen zahlreiche Experten als Ziel im primären Kompartiment Serum/Plasma, 60-100 % der Zeit eines Dosierungsintervalls, das 4-6-Fache der MHK bei β-Lactam-Antibiotika anzustreben [7,8,11,22,41,42].…”
Section: Bakterizider Effektunclassified
“…However, a MERINO sub-study observed no difference in mortality between PTZ and meropenem patients for isolates with a PTZ minimum inhibitory concentration (MIC) of <8 mg/L (291). This importance of pathogen MIC as a determinant of PTZ therapy supports investigation of different approaches to PTZ dosing to maximise bacterial killing and potentially improve patient outcomes (304).…”
Section: Introductionmentioning
confidence: 94%
“…Trough beta-lactam antibiotic concentrations of 2.5 to 4-fold the pathogen MIC has been associated with enhanced bacterial killing and the suppression of emergence of resistance in in vitro studies using intermittent infusion dosing regimens (30,287). These exposure targets have been supported by observational data where patient mortality was reduced when an unbound (free) beta-lactam concentration exceeds the pathogen minimum inhibitory concentration (MIC) throughout the dosing interval (100% fT>MIC) (89,304).…”
Section: Introductionmentioning
confidence: 99%